2023
DOI: 10.1007/s00464-023-10037-6
|View full text |Cite
|
Sign up to set email alerts
|

ST36 acupoint injection with anisodamine for postoperative nausea and vomiting in female patients after bariatric surgery: a prospective, randomized controlled trial

Abstract: Background The use of multimodal pharmacological prophylactic regimes has decreased postoperative nausea and vomiting (PONV) in general but it still occurs in over 60% of female patients after bariatric surgery. This study aimed to evaluate the efficacy of ST36 acupoint injection with anisodamine in prevention of PONV among female patients after bariatric surgery. Methods Ninety patients undergoing laparoscopic sleeve gastrectomy were randomly allocated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…These results suggest that ST36 acupoint injection not only improves the quality of postoperative recovery but also that the pharmacological effect of anisodamine enhances this therapeutic impact. Interestingly, another study found that ST36 acupoint injection without or with anisodamine had no effect on the early recovery in the hospital and quality of life after discharge [ 10 ]. The difference in the results of our analyses may be due to the inconsistency in the gender of the patients involved in the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that ST36 acupoint injection not only improves the quality of postoperative recovery but also that the pharmacological effect of anisodamine enhances this therapeutic impact. Interestingly, another study found that ST36 acupoint injection without or with anisodamine had no effect on the early recovery in the hospital and quality of life after discharge [ 10 ]. The difference in the results of our analyses may be due to the inconsistency in the gender of the patients involved in the study.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, ST36 acupoint injection of anisodamine has received increasing attention as a new therapeutic approach [ 9 ]. Studies have shown that ST36 acupoint injection of anisodamine has a good effect in improving PONV and other clinical adverse symptoms [ 10 ]. Therefore, the purpose of this study was to explore the effect of acupoint injection of anisodamine at ST36 on the quality of early recovery after bariatric surgery, in order to provide reference for clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…It is proven that the incorporation of ST36 acupoint injection with anisodamine yielded a significant reduction in postoperative vomiting among female patients with obesity who underwent laparoscopic sleeve gastrectomy, while not exerting any discernible impact on nausea. [82] In addition, Wang et al conducted a study demonstrating that the administration of anisodamine via acupoint injection can treat intractable hiccups following a stroke, and iacupoint injection of anisodamine combined with chlorpromazine produces superior outcomes for patients with intractable hiccups after stroke, while also exhibiting a high level of safety and potential for clinical application. [83] Numerous studies have demonstrated that the co-administration of anisodamine with conventional drug therapy yields enhanced therapeutic outcomes.…”
Section: Other Clinical Applicationsmentioning
confidence: 99%